The improvisation of musical dialogue: A phenomenology of music - Benson, Bruce Ellis (Cambridge Cambridge University Press, 2003)
Whereas most books on the philosophy of music focus on the creation and reproduction of music, Bruce Benson's concern is the phenomenology of music making as an activity. He offers a radical thesis that improvization is of primary importance at the moment of music making. The book brings together a wide range of musical examples from classical music, jazz, early music and other genres. Incorporating analytic and continental philosophy, musicology and performance-practice issues, it is a provocative study for philosophers of art and musicologists. It also appeals to general readers; especially those who perform.